2012
DOI: 10.1097/rlu.0b013e318263909a
|View full text |Cite
|
Sign up to set email alerts
|

Air Leaks Localized With Lung Ventilation SPECT

Abstract: A 61-year-old man with severe chronic obstructive pulmonary disease presented to our hospital with recurrence of a right-sided spontaneous secondary pneumothorax. Thoracoscopic abrasion of the parietal pleura was performed, but an important air leak persisted. Presumed to originate from a bulla in the right upper lobe, bullectomy and pleural decortication were performed, but leakage remained. Lobectomy was considered, and quantitative ventilation/perfusion SPECT was performed to predict the functional outcome.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…[13][14][15] Access to the Chest During surgical access to the chest, a breach in the visceral pleura and parenchyma may occur. Radionucleide imaging studies of pneumothorax suggest that particles as small as 5-10 nm may be released, 11,[18][19][20][21][22][23] which may be more significant if the underlying lung is subjected to positive pressure in the event of inadequate exclusion. The working group; therefore, recommended interrupting ventilation and using utmost care when opening the intercostal space or inserting an initial thoracoscopic trocar.…”
Section: Lung Isolation and Patient Positioningmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Access to the Chest During surgical access to the chest, a breach in the visceral pleura and parenchyma may occur. Radionucleide imaging studies of pneumothorax suggest that particles as small as 5-10 nm may be released, 11,[18][19][20][21][22][23] which may be more significant if the underlying lung is subjected to positive pressure in the event of inadequate exclusion. The working group; therefore, recommended interrupting ventilation and using utmost care when opening the intercostal space or inserting an initial thoracoscopic trocar.…”
Section: Lung Isolation and Patient Positioningmentioning
confidence: 99%
“…The working group emphasized the importance of air leak prevention, because pleural tears and parenchymal staple lines may leak air and generate aerosol when the lung is re-expanded under positive pressure. [19][20][21][22][23] Although their efficacy is somewhat controversial, the use of tissue reinforcement and/or tissue sealants may be considered to promote staple line integrity, 18,[29][30][31] as can limiting ventilation pressures because some evidence suggests this may reduce strain on staple lines. 31,32 Nevertheless, because the potential for air leak is inherent to lung surgery, the working group suggested that lung re-expansion proceed only once the pleural cavity has been excluded from the operating room environment.…”
Section: Conduct Of the Surgical Proceduresmentioning
confidence: 99%
“…Further work has shown this technique to be a viable approach to fistula localization (25,26). Incorporation of the radioisotope with concurrent CT imaging is regarded as SPECT/CT, whereby a CT is used to generate the post-inhalational images (27)(28)(29). One major limitation to both ventilation scintigraphy and SPECT/CT is reduced accuracy in parenchymal lung diseases such as chronic obstructive lung disease; in such diseases, turbulent parenchymal gas flow can lead to aerosol deposition in the distal parenchyma and generate a false-positive result.…”
Section: Nuclear Imagingmentioning
confidence: 99%
“…A similar examinations using a CT scanner except in a handful of experimental studies. [6][7][8][9][10][11] We refer to our new method as "saline-fi lled CT thoracography." Aside from contrast thoracography with fl uoroscopy 10,11 and experimental scintigraphic studies with special radioisotopes, 6,12-14 there exist few nonsurgical methods for detecting air leakage.…”
Section: Radiologic and Surgical Findingsmentioning
confidence: 99%